Jednorázová společnost? Sledování konzumních vzorců v urbánním prostředí - Brunclíková, Lenka; Sosna, Daniel (Lidé města, 2014)
Garbage is a considerable source of information that provides us with knowledge of not only what people consume, but also of how they dispose of the things they use. This paper focuses on the use of ethnography and garbology in order to identify the specific patterns of consumption in an urban area and shed light on the relationship between humans and waste. The chosen urban area is a neighbourhood called Vinice in Pilsen. The research questions focus on food wastage and on the identification of the conduits through which things flow away from households. The research was conducted at the landfill of municipal waste where the household waste was sorted, classified and described in detail. A modified method of quartering was applied for sampling. Over 1500 pieces of garbage, weighing more than 64 kg in total, were analysed. All data was recorded into a database in the field using a tablet. In order to complete the garbological data, an ethnographic survey was carried out in this area in the form of semi-structured interviews aimed at revealing the actors’ interpretation, classification of things and of garbage, and consumption practices. Although food wasting is perceived as unethical, it has become a habitual practice of everyday life. This practice is the result of consumers’ poor estimations of food consumption and their purchase of bargain-packages, as well as food-supplying strategies. Despite the considerable amount of potentially recyclable material that was mixed with solid waste, actors consider the recycling of waste as meaningful. Other ways of getting rid of things were also recognized, reflecting both the actors’ classification of things and their effort to eliminate the discarding of still-usable objects.